Shattered Barriers and Resilient Voices: Depictions of Discrimination in Peter Farrelly's Green Book (2018) - Faradissa, Tresananda Kirana; Laksono, Arido (Syntax Corporation, 2025)
Racial discrimination remains a pervasive issue in media representations, shaping societal perceptions and reinforcing systemic inequalities. The film Green Book (2018) portrays the racial discrimination experienced by Dr. Don Shirley, yet the deeper impact on his identity and social struggles requires further examination. This study aims to analyze the depiction of racial discrimination in Green Book and its effects on Shirley’s identity through a qualitative approach combining sociological theory and narrative film analysis. Data were collected from film dialogues, scenes, and academic literature and analyzed using discourse and cinematographic elements to reveal underlying social dynamics. Findings show that discrimination in the film is systemic, rooted in institutional and social structures that marginalize Shirley despite his cultural and economic capital. The film also perpetuates the “white savior” narrative, which diminishes Shirley’s agency by emphasizing Tony Lip’s role. Intersectionality reveals how overlapping factors of race, class, and masculinity shape Shirley’s experience. This study highlights the importance of nuanced media portrayals to challenge racial hierarchies and recommends further research on the influence of films on public perceptions of systemic racism.